1998
DOI: 10.1016/s0002-9270(98)00088-4
|View full text |Cite
|
Sign up to set email alerts
|

Complementary medicine use by patients with inflammatory bowel disease

Abstract: Complementary medicine use is common in patients with IBD, especially among those with a longer duration of disease or a history of hospitalization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
46
0

Year Published

2003
2003
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(53 citation statements)
references
References 7 publications
7
46
0
Order By: Relevance
“…[4] In comparison to that sample, our current sample is slightly older (mean age 46 vs. 40 years), contains fewer females (61% vs. 68%) and is better educated (73% vs. 64% with education beyond high-school degree). However, as expected, the current sample also contains more people with less severe Crohn's disease as shown by lower rate of hospitalizations (83% vs. 92%) and surgery (65% vs. 79%) and, although measured in different ways in the two studies, probably less use of oral and iv corticosteroids.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…[4] In comparison to that sample, our current sample is slightly older (mean age 46 vs. 40 years), contains fewer females (61% vs. 68%) and is better educated (73% vs. 64% with education beyond high-school degree). However, as expected, the current sample also contains more people with less severe Crohn's disease as shown by lower rate of hospitalizations (83% vs. 92%) and surgery (65% vs. 79%) and, although measured in different ways in the two studies, probably less use of oral and iv corticosteroids.…”
Section: Discussionmentioning
confidence: 97%
“…[4-8] Versions for adults (age 16 and above) and children were created. Only the results from the adult questionnaire are provided in this paper.…”
Section: Methodsmentioning
confidence: 99%
“…This value drops to 36% when prayer is excluded (6). Numerous studies have evaluated the use of CAM in the adult IBD population (79); however, the information on CAM in the pediatric population, most of which comes from countries other than the United States, is limited. US studies that used the 1996 Medical Expenditure Panel Survey database showed an overall prevalence of childhood CAM use between 1.8% and 2%, with an annual expenditure of $149 million on CAM visits and remedies (10,11).…”
mentioning
confidence: 99%
“…[71][72][73][74][75][76] British Society of Gastroenterology Guidance on IBD highlights the need for health care professionals to have a good knowledge of disease management and an understanding of the social and emotional impact of disease for patients and their families. 1 A cross-sectional study of patients attending a GI and general medical outpatient department identified that only 20% of patients with IBD were members of the National Association for Colitis and Crohn's Disease.…”
Section: Recommendationmentioning
confidence: 99%